Fundamental processes in sensorimotor learning: Reasoning, refinement, and retrieval - Jonathan S Tsay; Hyosub E Kim; Samuel D McDougle; Jordan A Taylor; Adrian Haith; Guy Avraham; John W Krakauer; Anne GE Collins; Richard B Ivry (eLife, 2024)
Motor learning is often viewed as a unitary process that operates outside of conscious awareness. This perspective has led to the development of sophisticated models designed to elucidate the mechanisms of implicit sensorimotor learning. In this review, we argue for a broader perspective, emphasizing the contribution of explicit strategies to sensorimotor learning tasks. Furthermore, we propose a theoretical framework for motor learning that consists of three fundamental processes: reasoning, the process of understanding action–outcome relationships; refinement, the process of optimizing sensorimotor and cognitive parameters to achieve motor goals; and retrieval, the process of inferring the context and recalling a control policy. We anticipate that this ‘3R’ framework for understanding how complex movements are learned will open exciting avenues for future research at the intersection between cognition and action.